FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PADA PERUSAHAAN PERTAMBANGAN - Albaihaqi, Ariq Adriel; Daud, Rulfah M; Afrianandra, Cut (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2025)
This study aims to analyze the influence of environmental performance, environmental costs, and corporate social responsibility disclosure. The population in this study consists of mining companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sampling technique used is purposive sampling, resulting in 15 mining companies that meet the predetermined criteria. The observation period for this study spans five years, leading to a total of 75 observational samples. The data used are secondary data sourced from annual reports and sustainability reports of mining companies listed on the Indonesia Stock Exchange (IDX) for the 20192023 period. The analytical method applied is multiple linear regression. The results show that the financial performance of mining companies listed on the Indonesia Stock Exchange from 2019 to 2023 is simultaneously influenced by environmental performance, environmental costs, and corporate social responsibility disclosure. Environmental performance does not affect the financial performance of mining companies listed on the Indonesia Stock Exchange from 2019 to 2023. Environmental costs do not affect the financial performance of mining companies listed on the Indonesia Stock Exchange from 2019 to 2023. However, corporate social responsibility disclosure affects the financial performance of mining companies listed on the Indonesia Stock Exchange from 2019 to 2023.